2021
DOI: 10.1111/liv.14970
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cholesterol metabolism underlies relative adrenal insufficiency in decompensated cirrhosis

Abstract: Background and Aims: Relative adrenal insufficiency (RAI) in patients with cirrhosis is associated with increased mortality. Although the pathogenesis of RAI remains unclear, disordered cholesterol metabolism may contribute. Methods:We performed a prospective cohort study of 96 non-critically ill subjects with decompensated cirrhosis at a tertiary care centre. Subjects were administered 250 µcg cosyntropin, with RAI defined as an increase in total cortisol <9 µg/dL. Highdensity lipoprotein (HDL) levels and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…Given these drawbacks, ACTH stimulation testing with TC levels continues to be the preferred diagnostic strategy to assess for AI in patients with cirrhosis given widespread clinical availability and rapid performance characteristics. Recent literature suggests adoption of delta cortisol rather than peak cortisol to diagnose RAI in cirrhosis because it implies a poor short-to-medium term prognosis, is less dependent on basal cortisol levels, and may provide a better assessment of adrenal responsiveness to acute stimuli (1,2,4). Free cortisol levels, if available, may be simultaneously obtained with TC levels to assess for underlying basal cortisol deficiency, although results may take up to 1–2 weeks given samples are often sent to an outside reference laboratory (1).…”
Section: How Should I Assess For Ai In Cirrhosis?mentioning
confidence: 99%
See 3 more Smart Citations
“…Given these drawbacks, ACTH stimulation testing with TC levels continues to be the preferred diagnostic strategy to assess for AI in patients with cirrhosis given widespread clinical availability and rapid performance characteristics. Recent literature suggests adoption of delta cortisol rather than peak cortisol to diagnose RAI in cirrhosis because it implies a poor short-to-medium term prognosis, is less dependent on basal cortisol levels, and may provide a better assessment of adrenal responsiveness to acute stimuli (1,2,4). Free cortisol levels, if available, may be simultaneously obtained with TC levels to assess for underlying basal cortisol deficiency, although results may take up to 1–2 weeks given samples are often sent to an outside reference laboratory (1).…”
Section: How Should I Assess For Ai In Cirrhosis?mentioning
confidence: 99%
“…Current pathophysiologic understanding of AI in cirrhosis is incomplete but may be multifactorial (1). Identified associations with abnormal cortisol responses in cirrhosis and inflammatory states include low HDL levels (adrenal substrate for steroidogenesis), decreased corticosteroid-binding globulin, and increased proinflammatory cytokines (including TNFa, IL-1, and IL-6), but their causality is not firmly established (1,3,9). Whether perturbations elsewhere along the HPA axis, adrenal enzymatic activity and/or steroidogenic pathway shunting, or dysregulation of systemic vascular tone contribute to RAI remain unknown (Figure 2).…”
Section: Pathophysiology Of Ai In Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…55 Furthermore, Wentworth et al have demonstrated that decreased HDL-C levels and diminished lecithincholesterol acyltransferase activity partially account for the development of RAI in decompensated cirrhotic patients. 56 They proposed that cholesterol metabolism impairment results in inadequate substrate delivery to the adrenal gland, which is responsible for normal steroidogenesis.…”
Section: Relative Adrenal Insufficiencymentioning
confidence: 99%